2012
DOI: 10.2147/iprp.s38102
|View full text |Cite
|
Sign up to set email alerts
|

Chronicles of a primary care practice pharmacist

Abstract: Background:In 2009, a pharmacist commenced working in a nondispensing role at a primary care medical center located in a metropolitan suburb of Brisbane, Australia. Research into the role and function of a practice pharmacist in this setting is still in its infancy. Methods: Ethnographic methods were used over a 3-month period to record activities undertaken by the practice pharmacist on a daily basis. Results: During the 3-month period, 296 hours of activity were documented. Activities the practice pharmacist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…differs from other typologies described by Farrell et al 2 and others, 3,4 where the practice pharmacist is physically located within the medical practice for the majority of the time.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…differs from other typologies described by Farrell et al 2 and others, 3,4 where the practice pharmacist is physically located within the medical practice for the majority of the time.…”
mentioning
confidence: 67%
“…While we happily acknowledge that comprehensive medication review is a central role of the practice pharmacist, it should not overshadow other roles that are just as significant. 4,5 Many of these roles are explored in the references cited by Angley et al while others can be drawn from the local and international literature.…”
mentioning
confidence: 99%
“…Research into the day-to-day role and function of general practice pharmacists is in its infancy, particularly in Australia. 3,4 In this pilot study, it was found that general practice pharmacists conducted activities that were, in order of decreasing time commitment, related to quality of practice, administration, medication review and patient education. Overall, two-thirds of their time was spent in clinically related duties.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of one Australian general practice pharmacist over a period of three months were reported by Freeman et al, who ascertained that the most common roles conducted were medication review, advice on the therapeutic management of individual patients, student supervision, drug information and administrative tasks. 4 To contribute to the limited Australian research on this topic, three general practices in the Australian Capital Territory (ACT) each employed a parttime, non-dispensing pharmacist in a pilot trial. This was an initiative of the Capital Health Network, ACT's Primary Health Network, who funded the payment of each pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Research in Australia has demonstrated the broad range of activities performed by pharmacists in general practice and shown effectiveness in resolving medicine-related problems and improving adherence. [13][14][15][16] In the United States, patientcentred medical home models have been established to provide comprehensive and coordinated primary care with integrated health care teams, including pharmacists. 17 In 2015, with the identification of benefits to both patients and practices by including pharmacists in primary care teams 5 and to counter a GP workload crisis, 18 England's National Health Service initiated the addition of pharmacists in general practice by recruiting 490 clinical pharmacists working across 650 GP practices.…”
Section: Introductionmentioning
confidence: 99%